2021
DOI: 10.1101/2021.03.08.434401
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerodynamics and motor control of ultrasonic vocalizations for social communication in mice and rats

Abstract: Rodent ultrasonic vocalizations (USVs) are crucial to their social communication and a widely used translational tool for linking gene mutations to behavior. To maximize the causal interpretation of experimental treatments, we need to understand how neural control affects USV production. However, both the aerodynamics of USV production and its neural control remain poorly understood. Here we test three intralaryngeal whistle mechanisms - the wall and alar edge impingement, and shallow cavity tone - by combinin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…Rat USVs are produced using a complex orchestration of the respiratory, laryngeal, and resonatory systems [45]. The whistle-like vocalization is produced by airflow passing through glottal and supraglottal spaces, and the configuration of these spaces can be altered by subglottic pressure and intrinsic laryngeal muscle activity [45][46][47][48]. Laryngeal motor innervation is primarily by the nucleus ambiguus through two divisions of the vagus nerve: superior and recurrent laryngeal nerves [49][50][51][52][53].…”
Section: Review Of Sex Differences 21 Sexual Dimorphism Of the Vocal Foldmentioning
confidence: 99%
See 1 more Smart Citation
“…Rat USVs are produced using a complex orchestration of the respiratory, laryngeal, and resonatory systems [45]. The whistle-like vocalization is produced by airflow passing through glottal and supraglottal spaces, and the configuration of these spaces can be altered by subglottic pressure and intrinsic laryngeal muscle activity [45][46][47][48]. Laryngeal motor innervation is primarily by the nucleus ambiguus through two divisions of the vagus nerve: superior and recurrent laryngeal nerves [49][50][51][52][53].…”
Section: Review Of Sex Differences 21 Sexual Dimorphism Of the Vocal Foldmentioning
confidence: 99%
“…Intrinsic laryngeal muscles such as the cricothyroid and thyroarytenoid elongate the glottis and shorten/close the vocal folds to regulate the glottal geometry for specific USV types [46]. Several studies have demonstrated that vocal fold approximation/configuration is critical for production and modulation of rat USVs, making rat vocal folds a targeted investigation in voicerelated research [46][47][48][54][55][56]. Additionally, rat vocal folds, like human vocal folds, are composed of a body (thyroarytenoid muscles) and cover (lamina propria, macula flavae, and epithelium) [57,58] and can produce audible vocalizations with vocal fold vibration in the frequency range 1-6 kHz [45,59,60].…”
Section: Review Of Sex Differences 21 Sexual Dimorphism Of the Vocal Foldmentioning
confidence: 99%